Coronavirus Infection Induced Coagulopathy As A Trigger Factor Of Arterial Thrombosis In Patient With Atherosclerotic Risk Factor: A Case Report - Irma Kamelia; Heny Martini; Novi Kurnianingsih; Indra Prasetya (Universitas Brawijaya, 2021)
Background : A newly emerging pandemic of Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory coronavirus 2 is responsible for significant morbidity and mortality worldwide. As one of the effects is hematological changes related to the COVID-19 infection causing patient tend to thrombosis than hemorrhagic. Current review of evidence and statements on management of coagulopathy and thrombotic complications related to this novel disease is needs to be exploredCase : Male 53 years old referred from Private Hospital, due to Severe pneumonia due to COVID-19 and Acute Limb Ischemia. This patient was assessed as Pneumonia COVID-19 severe with acute limb ischemia bilateral grade IIB and performed bilateral surgical thrombectomy with antegrade approach using fogarty catheter with the result was thrombus 10cm along the left femoral artery and thrombus 2cm in the right femoral artery. Discussion : With consideration of atherosclerotic diseases in this patient, we decided to give rivaroxaban as an anticoagulant combined with aspilet and statin high dose. But due to lack of source in our hospital, and patient also denied for further management, treatment for the patient cannot be optimal, so the patient discharge with unresolved limb ischemia.Conclusion : This case showed that the increase risk of heparin resistance in SARS-CoV-2 patient, it is recommend- ed to monitor heparin activity of UFH treatment based on anti-Xa levels instead of aPTT alone